Life cycle assessment of synthetic graphite: inventories and impact assessment - Mayanti, Bening (Springer, 2025)
The role of graphite has become more important as a material for batteries that support the decarbonization agenda. Synthetic graphite manufacturing is known for its intensive process; therefore, investigating its environmental impacts is crucial, as synthetic graphite dominates the market share of graphite. The environmental impacts were calculated using life cycle assessment (LCA) with a functional unit (FU) of producing 1 tonne of high-purity graphite for anode manufacturing from cradle-to-gate in China. The study reported an impact of 10.36 tonnes CO2 eq per FU. Contribution analysis revealed that graphitization accounted for 84% of the overall climate change impact across seven production stages. Scenario analysis, sensitivity analysis, and Monte Carlo simulation were applied to handle uncertainties in LCA. Electricity input was found to be the most sensitive parameter, and a Monte Carlo simulation that was run 10,000 times generated a 13% coefficient of variation. A comparison among studies was conducted to identify the causes of differences and improve reliability. The study presented comprehensive inventories for manufacturing synthetic graphite and demonstrated the importance of transparency, completeness, and reliability. The study may help stakeholders make informed decisions to improve the graphite and battery supply chain.
Keywords: Synthetic graphite; Anode material; Life cycle assessment; Life cycle inventory; Scenario analysis; Monte Carlo simulation; fi=Tuotantotalous kaupp|en=Industrial Management econ|